Performance evaluation of double type tuberose IIHR-4 (IC -0633777) for flower yield. quality and biotic stress resistance/tolerance - Bharathi, T U; Srinivas, Meenakshi; Umamaheswari, R; Sonavane, Priti (Journal of Horticultural Sciences, 2021)
An experiment was carried out to evaluate an advance breeding line of tuberose double type IIHR-4 along with check for flowering, yield and resistance to root knot nematode and Alternaria leaf burn disease. The hybrid selection IIHR-4 was developed through hybridization by crossing Mexican Single x Pearl Double, followed by selection. Double type tuberose IIHR-4 was found to be novel with better flowering and quality traits such as short spike (62.00 cm), rachis length (25.59cm), diameter of floret (4.47cm) and number of florets per spike (50.75). The spikes of IIHR-4 exhibited more number of florets open at a time in spike (7.10) with the shorter internodal length of 3.45cm. The florets are with shorter length (5.22cm) arranged very compactly on the spike making IIHR-4 ideal as cut flower. IIHR-4 was found to be highly resistant to root knot nematode Meloidogyne incognita under field conditions and tolerant to Alternaria leaf burn disease.
Keywords: Tuberose; Double Type; Flowering Yield; Cut Flower